Acrylic electrophoretic coating and preparation process thereof

The acrylic electrophoretic coating with modified aluminum phosphate and controlled preparation process addresses adhesion and curing issues, achieving improved adhesion and corrosion resistance with faster curing.

CN119220145AInactive Publication Date: 2024-12-31HEFEI WEICUAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311745731.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing electrophoretic coatings face issues such as poor adhesion to substrates, high shrinkage leading to damage, insufficient solvent dissolution, and uncontrolled drying times, along with high curing temperatures and long curing times.

Method used

An acrylic electrophoretic coating composition comprising specific main and auxiliary materials, including modified aluminum phosphate in the color paste, which reduces surface tension and enhances wetting and dispersion, along with a preparation process involving controlled addition of materials under nitrogen protection.

Benefits of technology

The coating exhibits improved adhesion, corrosion resistance, and uniformity, avoiding loose adhesion and water seepage, with enhanced stability and faster curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220145A_ABST
    Figure CN119220145A_ABST
Patent Text Reader

Abstract

The invention provides an acrylic acid electrophoretic coating and a preparation process thereof, the acrylic acid electrophoretic coating comprises main materials and auxiliary materials in corresponding parts by mass, the main materials comprise 5-15 parts by mass of acrylic acid, 10-15 parts by mass of ethylene-vinyl acetate copolymer, 2-5 parts by mass of styrene, 3-8 parts by mass of polydimethylsiloxane, 15-25 parts by mass of butanol, 3-8 parts by mass of benzoyl peroxide and 14-22 parts by mass of ethylene glycol monobutyl ether; the adhesive is prepared from the following components in parts by weight: 8 to 12 parts of hydroxypropyl methacrylate, 12 to 14 parts of methyl methacrylate, 6 to 8 parts of styrene, 14 to 17 parts of tert-butyl methacrylate, 4.5 to 7 parts of low-molecular-weight thioglycol, 3 to 5 parts of benzoyl peroxide and 3.5 to 7 parts of dimethylolpropionic acid. The acrylic acid electrophoretic paint has the advantages that by adding the modified aluminum phosphate and the auxiliary materials into the color paste, the surface tension between the color paste and water can be effectively reduced, the dispersion and stability of pigment and filler systems in the acrylic acid electrophoretic paint are facilitated, and the wetting and permeation of the acrylic acid electrophoretic paint on a base material are facilitated; the wetting, dispersing and stabilizing effects of the acrylic electrophoretic paint are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrophoretic coatings, in particular to an acrylic electrophoretic coating and a preparation process thereof. Background Art

[0002] In order to solve the problems that arise during the application process and meet the different requirements of different fields for coatings, the types of electrophoretic coatings are gradually enriched. Electrophoretic paints are divided into cathodic electrophoretic paints and anodic electrophoretic paints. Cathodic electrophoretic paints are divided into epoxy electrophoretic paints, acrylic electrophoretic paints and polyurethane electrophoretic paints, and anodic electrophoretic paints are anodic acrylic electrophoretic paints. Cathodic electrophoretic coating is a special coating method that uses an external electric field to make particles such as resins and pigments in water-based coatings migrate in a directional manner and deposit on the cathode substrate surface to form a film. Compared with other coating methods, such as roller coating, spray coating, and dipping coating, cathodic electrophoretic coating has the advantages of high coating utilization, high degree of automation, and excellent corrosion resistance of the paint film. It can also avoid the anode dissolution defects of anodic electrophoresis, which is more in line with the trend of green and environmentally friendly coatings.

[0003] However, in the application process of water-based electrophoretic coatings, some problems have also emerged accordingly, such as poor adhesion between the coating and the substrate, poor permeability of the resin, and internal stress caused by high volume shrinkage, which leads to damage of the coating and loss of its function of protecting the substrate; at the same time, traditional electrophoretic paint adopts thermal curing, which has high curing temperature and long curing time.

[0004] The composition and preparation method of a photocurable water-based acrylic cathode electrophoretic coating provided by publication number "CN109957299B". The base resin structure of the electrophoretic coating contains a benzyl ester structure, which is provided by benzyl acrylate. This photosensitive water-based acrylic resin can be radiation-cured by ultraviolet light irradiation. Compared with traditional thermal curing, this method is more energy-saving, environmentally friendly and rapid, and the coating can be applied to heat-sensitive substrates. The prepared coating has both certain anti-corrosion and decorative properties, and can be used in light anti-corrosion and decorative fields such as accessories, home appliances, and hardware.

[0005] However, the above device still has the following problems during implementation:

[0006] 1. The adhesion of the resin and monomer is not high and the shrinkage is too large. The coating is too thick and the curing is not thorough. The solvent is weak or evaporates too quickly, resulting in insufficient secondary dissolution of the primer: the surface tension is too high, the primer cannot be fully wetted and leveled, and the formula design is unreasonable;

[0007] 2. Acrylic paint and base layer use solvent-based adhesive, which is cold bonding. The drying time of the glue during the construction process is difficult to control. If the time is too long, the bonding will not be strong and will not meet the full adhesion standard, and water will occur. Summary of the invention

[0008] The object of the present invention is to provide an acrylic electrophoretic coating and a preparation process thereof to solve the problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] An acrylic electrophoretic coating comprises main materials and auxiliary materials in corresponding parts by weight, including the following main materials in parts by weight: 5-15 parts of acrylic acid, 10-15 parts of ethylene-vinyl acetate copolymer, 2-5 parts of styrene, 3-8 parts of epoxy resin, 3-8 parts of polydimethylsiloxane, 15-25 parts of butanol, 3-8 parts of benzoyl peroxide, 1-5 parts of isophorone, 10-21 parts of n-butanol, 14-22 parts of ethylene glycol monobutyl ether, 8-12 parts of hydroxypropyl methacrylate, 12-14 parts of methyl methacrylate, 6-8 parts of styrene, 14-17 parts of tert-butyl methacrylate, 4.5-7 parts of low molecular weight thiodiol, 3-5 parts of benzoyl peroxide and 3.5-7 parts of dimethylol propionic acid;

[0011] And auxiliary materials.

[0012] Preferably, the auxiliary materials include 8-15 parts of isocyanate curing agent, 6-9 parts of glycidyl methacrylate, 1-3 parts of film-forming solvent, 1-5 parts of surfactant, 20-35 parts of deionized water, and appropriate amounts of free radical initiator, catalyst, leveling agent, inhibitor and color paste.

[0013] Preferably, the color paste includes the following raw materials in parts by weight: 2.8-3.2 parts of barium sulfate, 0.55-0.65 parts of lemon yellow, 22-25 parts of phthalocyanine green, 33-35 parts of titanium dioxide, 2.2-2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol, 0.1-0.3 parts of ammonium persulfate, 0.5-0.7 parts of defoaming agent, 0.3-0.5 parts of color filler wetting agent, 7.2-7.6 parts of dispersant, 2.1-2.3 parts of solubilizing and moisturizing agent, and 1.5-1.8 parts of nano silicon dioxide.

[0014] Preferably, the solubilizing and moisturizing agent comprises sodium polyacrylate, sodium hyaluronate and polyethylene glycol-90M in parts by weight.

[0015] Preferably, the modified aluminum phosphate is prepared using 2.2-2.5 parts by mass of the above-mentioned sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol and 0.1-0.3 parts of ammonium persulfate.

[0016] Preferably, the preparation method of the modified aluminum phosphate comprises the following steps:

[0017] Sodium phosphate is dissolved in water to prepare a sodium phosphate solution with a mass fraction of 15%, and the solution is stirred. Dimethyl phosphite with a mass fraction of 3% of the sodium phosphate solution is added, and the solution is stirred at a high speed to be uniform and fully dissolved to obtain a solution A.

[0018] Dissolve aluminum chloride and polyethylene glycol in water to prepare a 15% by mass aluminum chloride solution;

[0019] The aluminum chloride solution was added into solution A at a volume ratio of 1:1, and then 0.02% of ammonium persulfate by mass of the aluminum chloride solution was added, and the mixture was stirred for 2 hours to obtain a turbid solution containing aluminum phosphate. The turbid solution was centrifuged, washed with water until neutral, and dried to obtain modified aluminum phosphate.

[0020] Preferably, the above stirring is carried out under the conditions of 80-100°C, 0.3-0.5MPa pressure and 1100-1300r / min rotation speed.

[0021] Preferably, the free radical initiator contains one or more of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, and tert-butyl hydroperoxide; the catalyst contains one or more of dibutyltin dilaurate, triethylenediamine, tetrabutylammonium hydrogensulfate, tetrabutylammonium bromide, and triethylbenzylammonium chloride; and the inhibitor is one or more of hydroquinone, p-benzoquinone, 2,6-di-tert-butyl-p-cresol, and p-tert-butylcatechol.

[0022] Preferably, the method for preparing the color paste comprises the following steps:

[0023] Mix 2.8-3.2 parts of barium sulfate, 0.55-0.65 parts of lemon yellow, 22-25 parts of phthalocyanine green, 33-35 parts of titanium dioxide, 2.2-2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol, 0.1-0.3 parts of ammonium persulfate, 0.5-0.7 parts of defoamer, 0.3-0.5 parts of pigment filler wetting agent, 7.2-7.6 parts of dispersant, 2.1-2.3 parts of solubilizing and moisturizing agent, and 1.5-1.8 parts of nano silicon dioxide uniformly according to the requirements in parts by mass, add 1 / 3 of the total amount of zirconium beads, grind at high speed for 1.0 hour under the condition of passing condensation water, special paint: color essence: water = 3:2:6, mix uniformly and disperse at high speed for 0.5 hour to obtain color paste.

[0024] The present invention also discloses a preparation process based on acrylic electrophoretic coating, comprising the following steps:

[0025] S1: Take acrylic acid, ethylene-vinyl acetate copolymer, styrene, epoxy resin, polydimethylsiloxane, butanol, benzoyl peroxide, isophorone, n-butanol, ethylene glycol monobutyl ether, hydroxypropyl methacrylate, methyl methacrylate, styrene, tert-butyl methacrylate, low molecular weight thiodiol, benzoyl peroxide and dimethylolpropionic acid in parts by mass, mix them evenly, pump all the mixed raw materials into the high-level reactor, and start heating the low-level reactor at the same time. When heated to 80°C, open the high-level reactor and add the mixture dropwise to the low-level reactor. The addition is completed within 2-4 hours, and then the temperature is kept at 85-110°C for 2.5-7 hours.

[0026] S2. Seal and evacuate the low-position reactor, add isocyanate curing agent, film-forming solvent, surfactant, deionized water, free radical initiator, catalyst, leveling agent, inhibitor and color paste according to the ratio, then fill with nitrogen for nitrogen protection, continue stirring, and then add glycidyl methacrylate several times. The addition is completed within 1.5-5 hours, and the reaction is kept at 85-110℃ for 3-8 hours to obtain a new type of acrylic electrophoretic coating.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. In the present invention, adding color paste to the auxiliary materials can effectively reduce the surface tension between the color paste and water, which is beneficial to the dispersion and stabilization of the pigment and filler system in the acrylic electrophoretic coating, and is beneficial to the wetting and penetration of the acrylic electrophoretic coating on the substrate. By adding modified aluminum phosphate to the color paste and the synergistic effect of the modified aluminum phosphate, the wetting, dispersion and stabilization effects of the acrylic electrophoretic coating are further improved;

[0029] 2. The color paste used as an auxiliary material in the present invention is small in amount, but has significant effects, good viscosity stability, good color development, and does not affect the surface gloss of the coating. In particular, the addition of modified aluminum phosphate can react with rust to form an insoluble heteropolyacid complex after hydrolysis of zinc chromate, thereby stabilizing rust. At the same time, it also reacts with the organic ammonia base in the formula to form a more insoluble complex polyacid complex to form a stable structure, thereby making the coating have better salt spray corrosion resistance. The color paste of the present invention has a higher solid content, stronger tinting power, better coating compatibility, strong adhesion, good hardness, and no coarsening;

[0030] 3. In the preparation process of the present invention, all the mixed raw materials are pumped into the high-level reactor, and after the low-level reactor is heated to a certain temperature, the high-level reactor is opened to drop the mixture into the low-level reactor, and the auxiliary materials are continuously added and stirred, and then the mixture is vacuumed and filled with nitrogen for nitrogen protection. The prepared coating is denser and smoother, and the situation of loose adhesion or water seepage due to too long a time is effectively avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a process flow chart for preparing an acrylic electrophoretic coating. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The present invention provides a technical solution:

[0034] Embodiment 1:

[0035] An acrylic electrophoretic coating, comprising a main material and auxiliary materials in corresponding weight parts,

[0036] The invention comprises the following main ingredients in parts by weight: 5 parts of acrylic acid, 10 parts of ethylene-vinyl acetate copolymer, 2 parts of styrene, 3 parts of epoxy resin, 3 parts of polydimethylsiloxane, 15 parts of butanol, 3 parts of benzoyl peroxide, 1 part of isophorone, 10 parts of n-butanol, 14 parts of ethylene glycol monobutyl ether, 8 parts of hydroxypropyl methacrylate, 12 parts of methyl methacrylate, 6 parts of styrene, 14 parts of tert-butyl methacrylate, 4.5 parts of low molecular weight thioglycol, 3 parts of benzoyl peroxide and 3.5 parts of dimethylolpropionic acid;

[0037] And auxiliary materials.

[0038] The auxiliary materials include 8 parts of isocyanate curing agent, 6 parts of glycidyl methacrylate, 1 part of film-forming solvent, 1 part of surfactant, 20 parts of deionized water, and appropriate amounts of free radical initiator, catalyst, leveling agent, inhibitor and color paste.

[0039] The free radical initiator contains one or more of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, and tert-butyl hydroperoxide; the catalyst contains one or more of dibutyltin dilaurate, triethylenediamine, tetrabutylammonium hydrogensulfate, tetrabutylammonium bromide, and triethylbenzylammonium chloride; and the inhibitor is one or more of hydroquinone, p-benzoquinone, 2,6-di-tert-butyl-p-cresol, and p-tert-butylcatechol.

[0040] The color paste includes the following raw materials in parts by mass: 2.8 parts of barium sulfate, 0.55 parts of lemon yellow, 22 parts of phthalocyanine green, 33 parts of titanium dioxide, 2.2 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1 part of aluminum chloride, 1 part of polyethylene glycol, 0.1 part of ammonium persulfate, 0.5 parts of defoaming agent, 0.3 parts of color filler wetting agent, 7.2 parts of dispersant, 2.1 parts of solubilizing and moisturizing agent, and 1.5 parts of nano silicon dioxide.

[0041] The dissolution-aiding moisturizing agent comprises sodium polyacrylate, sodium hyaluronate and polyethylene glycol-90M in parts by weight.

[0042] Modified aluminum phosphate is prepared by using the above-mentioned parts by mass of sodium phosphate, an appropriate amount of dimethyl phosphite, aluminum chloride, polyethylene glycol and ammonium persulfate.

[0043] The preparation method of the modified aluminum phosphate comprises the following steps:

[0044] Sodium phosphate is dissolved in water to prepare a sodium phosphate solution with a mass fraction of 15%, and the solution is stirred. Dimethyl phosphite with a mass fraction of 3% of the sodium phosphate solution is added, and the solution is stirred at a high speed to be uniform and fully dissolved to obtain a solution A.

[0045] Dissolve aluminum chloride and polyethylene glycol in water to prepare a 15% by mass aluminum chloride solution;

[0046] The aluminum chloride solution is added to solution A at a volume ratio of 1:1, and then ammonium persulfate of 0.02% of the mass of the aluminum chloride solution is added, and stirred for reaction for 2 hours to obtain a turbid solution containing aluminum phosphate, and the turbid solution is centrifuged, washed with water until neutral, and dried to obtain modified aluminum phosphate. It should be noted that the stirring is carried out at 80-100°C, 0.3-0.5MPa pressure, and 1100-1300r / min speed.

[0047] The color paste preparation method comprises the following steps:

[0048] Mix 2.8-3.2 parts of barium sulfate, 0.55-0.65 parts of lemon yellow, 22-25 parts of phthalocyanine green, 33-35 parts of titanium dioxide, 2.2-2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol, 0.1-0.3 parts of ammonium persulfate, 0.5-0.7 parts of defoamer, 0.3-0.5 parts of pigment filler wetting agent, 7.2-7.6 parts of dispersant, 2.1-2.3 parts of solubilizing and moisturizing agent, and 1.5-1.8 parts of nano silicon dioxide uniformly according to the requirements in parts by mass, add 1 / 3 of the total amount of zirconium beads, grind at high speed for 1.0 hour under the condition of passing condensation water, special paint: color essence: water = 3:2:6, mix uniformly and disperse at high speed for 0.5 hour to obtain color paste.

[0049] It should be noted that, due to the small amount of color paste, it is configured as an auxiliary material. However, the present invention can effectively reduce the surface tension between the color paste and water by adding the color paste, which is beneficial to the dispersion and stabilization of the pigment and filler system in the acrylic electrophoretic coating, and is beneficial to the wetting and penetration of the acrylic electrophoretic coating into the substrate. By adding modified aluminum phosphate to the color paste, the wetting, dispersion and stabilization effects of the acrylic electrophoretic coating are further improved.

[0050] Embodiment 2:

[0051] The difference from the first embodiment is that:

[0052] An acrylic electrophoretic coating, comprising a main material and auxiliary materials in corresponding weight parts,

[0053] The invention comprises the following main ingredients in parts by mass: 10 parts of acrylic acid, 12 parts of ethylene-vinyl acetate copolymer, 3.5 parts of styrene, 5 parts of epoxy resin, 5 parts of polydimethylsiloxane, 20 parts of butanol, 5 parts of benzoyl peroxide, 3 parts of isophorone, 15 parts of n-butanol, 18 parts of ethylene glycol monobutyl ether, 10 parts of hydroxypropyl methacrylate, 13 parts of methyl methacrylate, 7 parts of styrene, 15 parts of tert-butyl methacrylate, 5.5 parts of low molecular weight thioglycol, 4 parts of benzoyl peroxide and 5 parts of dihydroxymethylpropionic acid.

[0054] The auxiliary materials include 12 parts of isocyanate curing agent, 8 parts of glycidyl methacrylate, 2 parts of film-forming solvent, 3 parts of surfactant, 28 parts of deionized water, and appropriate amounts of free radical initiator, catalyst, leveling agent, inhibitor and color paste.

[0055] The color paste preparation method comprises the following steps:

[0056] Mix 3 parts of barium sulfate, 0.6 parts of lemon yellow, 24 parts of phthalocyanine green, 34 parts of titanium dioxide, 2.4 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1.3 parts of aluminum chloride, 1.3 parts of polyethylene glycol, 0.2 parts of ammonium persulfate, 0.6 parts of defoamer, 0.4 parts of pigment and filler wetting agent, 7.4 parts of dispersant, 2.2 parts of solubilizing agent and 1.6 parts of nano-silicon dioxide uniformly according to the required mass parts, add 1 / 3 of the total amount of zirconium beads, grind at high speed for 1.0 h under the condition of passing condensation water, special paint: color essence: water = 3:2:6, mix uniformly and disperse at high speed for 0.5 h to obtain color paste.

[0057] Embodiment three:

[0058] The difference from the first embodiment is that:

[0059] An acrylic electrophoretic coating, comprising a main material and auxiliary materials in corresponding weight parts,

[0060] The invention comprises the following main ingredients in parts by mass: 15 parts of acrylic acid, 15 parts of ethylene-vinyl acetate copolymer, 5 parts of styrene, 8 parts of epoxy resin, 8 parts of polydimethylsiloxane, 25 parts of butanol, 8 parts of benzoyl peroxide, 5 parts of isophorone, 21 parts of n-butanol, 22 parts of ethylene glycol monobutyl ether, 12 parts of hydroxypropyl methacrylate, 14 parts of methyl methacrylate, 8 parts of styrene, 17 parts of tert-butyl methacrylate, 7 parts of low molecular weight thiodiol, 5 parts of benzoyl peroxide and 7 parts of dimethylolpropionic acid.

[0061] The auxiliary materials include 15 parts of isocyanate curing agent, 9 parts of glycidyl methacrylate, 3 parts of film-forming solvent, 5 parts of surfactant, 35 parts of deionized water, and appropriate amounts of free radical initiator, catalyst, leveling agent, inhibitor and color paste.

[0062] The color paste preparation method comprises the following steps:

[0063] Mix 3.2 parts of barium sulfate, 0.65 parts of lemon yellow, 25 parts of phthalocyanine green, 35 parts of titanium dioxide, 2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1.5 parts of aluminum chloride, 1.5 parts of polyethylene glycol, 0.3 parts of ammonium persulfate, 0.7 parts of defoamer, 0.5 parts of pigment and filler wetting agent, 7.6 parts of dispersant, 2.3 parts of solubilizing agent and 1.8 parts of nano-silicon dioxide uniformly according to the required mass parts, add 1 / 3 of the total amount of zirconium beads, grind at high speed for 1.0 h under the condition of passing condensation water, special paint: color essence: water = 3:2:6, mix uniformly and disperse at high speed for 0.5 h to obtain color paste.

[0064] Table 1, when implemented according to Example 1 to Example 3, the formula composition is as follows:

[0065]

[0066]

[0067] See also Figure 1 The present invention also discloses a preparation process, based on the above-mentioned acrylic electrophoretic coating, comprising the following steps:

[0068] S1: Take acrylic acid, ethylene-vinyl acetate copolymer, styrene, epoxy resin, polydimethylsiloxane, butanol, benzoyl peroxide, isophorone, n-butanol, ethylene glycol monobutyl ether, hydroxypropyl methacrylate, methyl methacrylate, styrene, tert-butyl methacrylate, low molecular weight thiodiol, benzoyl peroxide and dimethylolpropionic acid in parts by mass, mix them evenly, pump all the mixed raw materials into the high-level reactor, and start heating the low-level reactor at the same time. When heated to 80°C, open the high-level reactor and add the mixture dropwise to the low-level reactor. The addition is completed within 2-4 hours, and then the temperature is kept at 85-110°C for 2.5-7 hours.

[0069] S2. Seal and evacuate the low-position reactor, add isocyanate curing agent, film-forming solvent, surfactant, deionized water, free radical initiator, catalyst, leveling agent, inhibitor and color paste according to the ratio, then fill with nitrogen for nitrogen protection, continue stirring, and then add glycidyl methacrylate several times. The addition is completed within 1.5-5 hours, and the reaction is kept at 85-110℃ for 3-8 hours to obtain a new type of acrylic electrophoretic coating.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An acrylic electrophoretic coating, comprising corresponding parts by weight of a main material and auxiliary materials, characterized in that: The invention comprises the following main materials in parts by weight: 5-15 parts of acrylic acid, 10-15 parts of ethylene-vinyl acetate copolymer, 2-5 parts of styrene, 3-8 parts of epoxy resin, 3-8 parts of polydimethylsiloxane, 15-25 parts of butanol, 3-8 parts of benzoyl peroxide, 1-5 parts of isophorone, 10-21 parts of n-butanol, 14-22 parts of ethylene glycol monobutyl ether, 8-12 parts of hydroxypropyl methacrylate, 12-14 parts of methyl methacrylate, 6-8 parts of styrene, 14-17 parts of tert-butyl methacrylate, 4.5-7 parts of low molecular weight thiodiol, 3-5 parts of benzoyl peroxide and 3.5-7 parts of dimethylol propionic acid; And auxiliary materials.

2. An acrylic electrophoretic coating according to claim 1, characterized in that: The auxiliary materials include 8-15 parts of isocyanate curing agent, 6-9 parts of glycidyl methacrylate, 1-3 parts of film-forming solvent, 1-5 parts of surfactant, 20-35 parts of deionized water, and appropriate amounts of free radical initiator, catalyst, leveling agent, inhibitor and color paste.

3. An acrylic electrophoretic coating according to claim 2, characterized in that: The color paste comprises the following raw materials in parts by weight: 2.8-3.2 parts of barium sulfate, 0.55-0.65 parts of lemon yellow, 22-25 parts of phthalocyanine green, 33-35 parts of titanium dioxide, 2.2-2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol, 0.1-0.3 parts of ammonium persulfate, 0.5-0.7 parts of defoaming agent, 0.3-0.5 parts of color filler wetting agent, 7.2-7.6 parts of dispersant, 2.1-2.3 parts of solubilizing and moisturizing agent, and 1.5-1.8 parts of nano silicon dioxide.

4. The acrylic electrophoretic coating according to claim 3, characterized in that: The dissolution-aiding moisturizing agent comprises sodium polyacrylate, sodium hyaluronate and polyethylene glycol-90M in parts by weight.

5. The acrylic electrophoretic coating according to claim 3, characterized in that: Modified aluminum phosphate is prepared using 2.2-2.5 parts by mass of the above-mentioned sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol and 0.1-0.3 parts of ammonium persulfate.

6. The acrylic electrophoretic coating according to claim 5, characterized in that: The preparation method of the modified aluminum phosphate comprises the following steps: Sodium phosphate is dissolved in water to prepare a sodium phosphate solution with a mass fraction of 15%, and the solution is stirred. Dimethyl phosphite with a mass fraction of 3% of the sodium phosphate solution is added, and the solution is stirred at a high speed to be uniform and fully dissolved to obtain a solution A. Dissolve aluminum chloride and polyethylene glycol in water to prepare a 15% by mass aluminum chloride solution; The aluminum chloride solution was added into solution A at a volume ratio of 1:1, and then 0.02% of ammonium persulfate by mass of the aluminum chloride solution was added, and the mixture was stirred for 2 hours to obtain a turbid solution containing aluminum phosphate. The turbid solution was centrifuged, washed with water until neutral, and dried to obtain modified aluminum phosphate.

7. The acrylic electrophoretic coating according to claim 6, characterized in that: The above stirring is carried out under the conditions of 80-100°C, 0.3-0.5MPa pressure and 1100-1300r / min rotation speed.

8. The acrylic electrophoretic coating according to claim 2, characterized in that: The free radical initiator contains one or more of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, and tert-butyl hydroperoxide; the catalyst contains one or more of dibutyltin dilaurate, triethylenediamine, tetrabutylammonium hydrogensulfate, tetrabutylammonium bromide, and triethylbenzylammonium chloride; and the inhibitor is one or more of hydroquinone, p-benzoquinone, 2,6-di-tert-butyl-p-cresol, and p-tert-butylcatechol.

9. The acrylic electrophoretic coating according to claim 3, characterized in that: The color paste preparation method comprises the following steps: Mix 2.8-3.2 parts of barium sulfate, 0.55-0.65 parts of lemon yellow, 22-25 parts of phthalocyanine green, 33-35 parts of titanium dioxide, 2.2-2.5 parts of sodium phosphate, an appropriate amount of dimethyl phosphite, 1-1.5 parts of aluminum chloride, 1-1.5 parts of polyethylene glycol, 0.1-0.3 parts of ammonium persulfate, 0.5-0.7 parts of defoamer, 0.3-0.5 parts of pigment filler wetting agent, 7.2-7.6 parts of dispersant, 2.1-2.3 parts of solubilizing and moisturizing agent, and 1.5-1.8 parts of nano silicon dioxide uniformly according to the mass requirements, add 1 / 3 of the total amount of zirconium beads, and grind at high speed for 1.0h under the condition of passing condensation water. Special paint: color essence: water = 3:2:6, mix uniformly and disperse at high speed for 0.5h to obtain color paste.

10. A preparation process, based on an acrylic electrophoretic coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Take acrylic acid, ethylene-vinyl acetate copolymer, styrene, epoxy resin, polydimethylsiloxane, butanol, benzoyl peroxide, isophorone, n-butanol, ethylene glycol monobutyl ether, hydroxypropyl methacrylate, methyl methacrylate, styrene, tert-butyl methacrylate, low molecular weight thiodiol, benzoyl peroxide and dimethylolpropionic acid in parts by mass, mix them evenly, pump all the mixed raw materials into the high-level reactor, and start heating the low-level reactor at the same time. When heated to 80°C, open the high-level reactor and add the mixture dropwise to the low-level reactor. The addition is completed within 2-4 hours, and then the temperature is kept at 85-110°C for 2.5-7 hours. S2. Seal and evacuate the low-position reactor, add isocyanate curing agent, film-forming solvent, surfactant, deionized water, free radical initiator, catalyst, leveling agent, inhibitor and color paste according to the ratio, then fill with nitrogen for nitrogen protection, continue stirring, and then add glycidyl methacrylate several times. The addition is completed within 1.5-5 hours, and the reaction is kept at 85-110℃ for 3-8 hours to obtain a new type of acrylic electrophoretic coating.